Peningkatan Partisipasi Pembelajaran Menggunakan Media Digital - Supriyanto (Prosiding Temu Ilmiah Nasional Guru, 2022)
This study aims to increase the participation and active role of students in participating in the learning process, especially during the COVID-19 pandemic. The focus of this research is the students of grade 6.a State Elementary School 14 Indralaya Utara. Data collection techniques using questionnaires, interviews and observations. The purpose of this paper is to describe digital media facilities in class 6.a learning at State Elementary School 14 Indralaya Utara during the COVID-19 pandemic in the 2021/2022 school year. From the data obtained, it turns out that before learning using digital media was carried out, only 11 students were actively involved in participating in learning. After learning by using digital media 23 out of 25 students were actively involved in the learning process.